Seed Production of Leavenworth's Coreopsis - Jeffrey G. Norcini (EDIS, 2002)
This document is ENH 868, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date September 2002; revised August 2006.